25 Trans-catheter reconstruction of native interrupted aortic arch in adults. (28th April 2017) - Kudumula, Vikram; Taliotis, Demetris; Velasco-Sanchez, Danial; MacDonald, Simon; Duke, Abdul Karim
Abstract : Transcatheter stenting is widely accepted treatment for coarctation of aorta in adolescents and adults, but stenting of interrupted aortic arch (IAA) is very challenging. We report 2 cases of adults, who had successful percutaneous reconstruction of IAA in our institute. Case 1 (33 year old) and case 2 (52 year old) presented with resistant systemic hypertension and subsequently diagnosed as having IAA in MRI scan. Right radial and right femoral arterial access was gained in both cases. Simultaneous angiograms in proximal and distal aortic segments confirmed IAA distal to the left subclavian artery, with a short atretic segment. After multiple failed attempts to cross the atretic segment by 0.035" Terumo wire and coronary guide wires, the atretic segment in both the cases was crossed by using radiofrequency (RF) guidewire ((Baylis MedComp Inc, Montreal, Canada). We crossed the atretic segment retrogradely from descending aorta in case 1 and antegradely from aortic arch in case 2 (Figures 1, 2). We snared the RF wire with goose neck snare and created an artero-arterial circuit. We placed the Amplatzer superstiff wire in the right subclavian artery and deployed 45mm length covered Cheatham platinum stents (NuMED Canada Inc, Canada) across the atretic segment in both the cases. Final angiogram showed good stent position with no complications and the pressure gradient across the stent was 2 mmHg. The echocardiograms 24 hours after the procedures were satisfactory with no complications.